SIFAT SENSORY BISKUIT BERBAHAN BAKU TEPUNG JAGUNG TERNIKSTAMALSASI DAN TERIGU - Siti Nurdjanah; Sussi Astuti; Nanti Musita; Tri Febriyaningsih (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
The objective of this research was to find the  the best ratio between nixtamalized corn flour and wheat flour to produce biscuits with the best sensory properties.  The experiment was a single factor, arranged in a complete randomized block design  with five replications.  The the treatment was the formulation nixtamalized of corn flour and wheat flour, consisted of 5 levels: 100:0 (F1), 90:10 (F2), 80:20 (F3), 70:30 (F4), and 60:40 (F5).  The data were analyzed using ANOVA and further tested with LSD at 5% level of significance. The results showed that the proportion of nixtamalized corn flour and wheat flour significanly influenced the flavor, color, texture, and overall acceptance of biscuits.  The best treatment was found biscuits in the produced from 100% nixtamalized corn flour (F1) with flavor score of 3.67 (typical corn), color score of 4.30 (yellow), texture score of 3.94 (compact), and overall acceptance score at 3:58 (like). These results indicated that nixtamalized corn flour could be used  to replace 100% of wheat flour in the manufacture of biscuits. Keywords: biscuits, nixtamalized corn flour